2012
DOI: 10.1080/0305764x.2012.676627
|View full text |Cite
|
Sign up to set email alerts
|

Ambience in social learning: student engagement with new designs for learning spaces

Abstract: An imperative to develop the social experience of learning has led to the design of informal learning spaces within libraries. Yet little is known about how these spaces are used by students or how students perceive them. Field work in one such space is reported. The general private study practice of undergraduates was captured through audio diaries, while activity in the learning space was directly observed, and students provided reflective perspectives in focus groups and through spot conversations. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 16 publications
(11 reference statements)
1
31
0
Order By: Relevance
“…Methods such as interviews and surveys are still employed (Bennett 2011;May and Swabey 2015;Yoolee et al 2013), but it is has pushed researchers to employ more novel, creative and participatory methods: especially observation, log books and ethnographic methods (Bryant et al 2009;Crook and Mitchell 2012;May and Swabey 2015;Hunter and Cox 2014) but also visual and mapping methods (Cox 2011;Harrop and Turpin 2013). This reflects a move from a model of measuring student satisfaction, to a more open-ended need to explore the experience of learning that calls for richer qualitative data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods such as interviews and surveys are still employed (Bennett 2011;May and Swabey 2015;Yoolee et al 2013), but it is has pushed researchers to employ more novel, creative and participatory methods: especially observation, log books and ethnographic methods (Bryant et al 2009;Crook and Mitchell 2012;May and Swabey 2015;Hunter and Cox 2014) but also visual and mapping methods (Cox 2011;Harrop and Turpin 2013). This reflects a move from a model of measuring student satisfaction, to a more open-ended need to explore the experience of learning that calls for richer qualitative data.…”
Section: Methodsmentioning
confidence: 99%
“…Harrop and Turpin 2013;May and Swabey 2015;Ojennus and Watts 2015), particularly newly designed areas for collaborative work (Bryant et al 2009;Matthews et al 2011;Crook and Mitchell 2012) and what underpins student preferences as a whole (Yoo-Lee et al 2013).…”
Section: Student Use Of Learning Spacesmentioning
confidence: 99%
“…Webb et al (2008) noted through observation that 70% of the students were engaged in individual study (p. 416). Crook and Mitchell (2012) observed that approximately 50% of students were engaged in individual study while the rest were engaged in conversation of some variety (p. 128). This diversity of activities in libraries may best be summed up by Montgomery (2011), who ascertained that students "want to study alone but still need space to meet in groups" (p. 84).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Others have employed a mixed methodology, using several of these approaches to answer their research questions. For example, Pierard and Lee (2011) employed photo diaries, flipcharts, and a traditional user survey in their study, and Crook and Mitchell (2012) employed observation, audio diaries, and focus groups, while Foster and Gibbons (2007) used interviews, maps, photographs, and flipcharts. These less traditional means for obtaining feedback are considered ethnographic approaches.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation